2016
DOI: 10.1103/physrevb.94.165115
|View full text |Cite
|
Sign up to set email alerts
|

Extended nuclear quadrupole resonance study of the heavy-fermion superconductorPuCoGa5

Abstract: PuCoGa5 has emerged as a prototypical heavy-fermion superconductor, with its transition temperature (Tc ≃ 18.5 K) being the highest amongst such materials. Nonetheless, a clear description as to what drives the superconducting pairing is still lacking, rendered complicated by the notoriously intricate nature of plutonium's 5f valence electrons. Here, we present a detailed 69,71 Ga nuclear quadrupole resonance (NQR) study of PuCoGa5, concentrating on the system's normal state properties near to Tc and aiming to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These results have been interpreted as evidence for a valence transition at a T V < T c that is avoided by the superconducting state [14]. On the other hand, the relaxation rate isotope ratio T [15] that could, nevertheless, be associated with charge (valence) fluctuations with a higher energy scale. High-resolution powder x-ray-diffraction recently showed that the volume expansion of PuCoGa 5 deviates from the curve expected for a simple Grüneisen-Einstein model, but the observed variations are too small to be taken as an indication for the proximity of the system to a valence instability [16].…”
mentioning
confidence: 90%
“…These results have been interpreted as evidence for a valence transition at a T V < T c that is avoided by the superconducting state [14]. On the other hand, the relaxation rate isotope ratio T [15] that could, nevertheless, be associated with charge (valence) fluctuations with a higher energy scale. High-resolution powder x-ray-diffraction recently showed that the volume expansion of PuCoGa 5 deviates from the curve expected for a simple Grüneisen-Einstein model, but the observed variations are too small to be taken as an indication for the proximity of the system to a valence instability [16].…”
mentioning
confidence: 90%
“…Beyond characterizing QN spin systems, NQR spectroscopy has proven its scientific versatility in several applications and studies as, for example, research on molecular structure [66,67], superconductors [68], semiconductors [69], and phase transitions [70,71], as well as quantum computing [72] and the authentication of medicines [73].…”
Section: A Nqr Spectroscopymentioning
confidence: 99%
“…In fact, a comparison between the properties of PuCoGa 5 and PuCoIn 5 has suggested two distinct electron pairing mechanisms, one due to spin fluctuations and the other mediated by valence fluctuations. 11,12 Although the electron pairing mechanism is still under debate, more recent experiments clearly evidence a d-wave superconductivity in PuCoGa 5 . 13 Early theoretical works employed different methods to study the electronic structure of PuCoGa 5 .…”
Section: Introductionmentioning
confidence: 99%